2010
DOI: 10.1105/tpc.109.072959
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide–Mediated Activation of MAP Kinase 6 Modulates Nitric Oxide Biosynthesis and Signal Transduction inArabidopsis 

Abstract: Nitric oxide (NO) is a bioactive molecule that functions in numerous physiological and developmental processes in plants, including lateral root development. In this study, we used biochemical and genetic approaches to analyze the function of Arabidopsis thaliana mitogen-activated protein kinase 6 (MPK6) in the regulation of NO synthesis in response to hydrogen peroxide (H 2 O 2 ) during lateral root development. In both mpk6 mutants studied, H 2 O 2 -induced NO synthesis and nitrate reductase (NR) activity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
203
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(218 citation statements)
references
References 102 publications
13
203
1
1
Order By: Relevance
“…We suggest that there is an interaction between H 2 O 2 and NO, and H 2 O 2 may modulate the NO signal during mung bean responses to 3-O-C10-HL stimulation. This conclusion is consistent with previous findings that H 2 O 2 regulates NO metabolism in Arabidopsis (Wang et al, 2010).…”
Section: The Cross Talk Of H 2 O 2 No and Cgmp May Mediate 3-o-c10supporting
confidence: 83%
“…We suggest that there is an interaction between H 2 O 2 and NO, and H 2 O 2 may modulate the NO signal during mung bean responses to 3-O-C10-HL stimulation. This conclusion is consistent with previous findings that H 2 O 2 regulates NO metabolism in Arabidopsis (Wang et al, 2010).…”
Section: The Cross Talk Of H 2 O 2 No and Cgmp May Mediate 3-o-c10supporting
confidence: 83%
“…Hence, both NO and ET participate in up-regulation of plasma membrane H + -ATPase that modulates ion homeostasis for improved salt tolerance. NO and ET also cooperate to stimulate the alternative respiratory pathway under salt stress conditions [91,92]. Contrary reports of Poór and Tari [85] showed antagonistic relationship between NO and ET in tomato cell suspension cultures treated with NaCl (100 and 250 mM).…”
Section: No-phytohormone Cross Talk Under Salinity Stresscontrasting
confidence: 39%
“…Furthermore, several reports have suggested that NR activity can be modulated at the posttranscriptional level. For example, H 2 O 2 is required for the activation of mitogen-activated protein kinase (MAPK) 6, which can subsequently increase NR activity by phosphorylation of NIA2 at Ser-627 (Wang et al, 2010a). Also, NIA2 can be phosphorylated by a calcium-dependent protein kinase at Ser-534 in the hinge 1 region in response to light and other environmental signals (Su et al, 1996).…”
Section: Discussionmentioning
confidence: 99%